Analisis Hubungan Promosi dengan Minat Beli Wisatawan terhadap Produk Olahan Komoditas Carica di Dataran Tinggi Dieng - Ernes Septina Azizi; Karyna Yulia Dwi A’nisya (Tumbuhan : Publikasi Ilmu Sosiologi Pertanian Dan Ilmu Kehutanan, 2024)
Currently, social media is considered a convenient tool for facilitating product transactions. However, not all marketers possess effective strategies for promoting their products on social media. This study aims to analyze the relationship between promotion and tourists’ purchase intention toward processed carica products in the Dieng Highlands. The research was conducted from February to March 2024, involving 100 respondents and analyzed using simple linear regression. The findings reveal a significant relationship between promotion and tourists’ purchase intention toward processed carica products in the Dieng Highlands. Promotion contributed 30.5% to purchase intention, while the remaining 69.5% was influenced by other factors outside the scope of this study. Carica-based MSMEs in the Dieng Highlands optimize their promotion strategies through tourist recommendations and digital marketing. They actively use social media platforms such as Facebook, Instagram, and TikTok and market their products through e-commerce platforms like Shopee, Tokopedia, and TikTok Shop. These efforts aim to enhance accessibility, attract consumer interest, and expand market reach.